Blade Element Momentum simulations using polars extracted from wind-turbine-model experiments - Rodrigues, Pedro Trombini [UNESP]; Lemos, Diego Magela; Pagani Júnior, Carlos do Carmo [UNESP]; Sampaio, Daniel Souza [UNESP] (ABCM, 2021)
Due to rotational effects, the observed load of inboard sections of rotary wings is consistently higher than the load predicted based on the two-dimensional aerodynamic behavior of the corresponding airfoil in linear motion. Therefore, engineering methods used to analyze and optimize the aerodynamics of horizontal-axis wind turbines (HAWT) rely on corrections to 2D airfoil data. Since the physics associated with the phenomenon is not fully understood, the correction models have to resort to empirically determined parameters. It is important to stress that a great scattering of the turbine power predictions based on different correction models is observed for conditions of high blade load. We propose a methodology to predict the load on HAWT blades based on the widely applied blade element momentum (BEM) method that does not rely on the correction of 2D polar curves. In the proposed methodology, the force coefficients are stored in the lookup table and consulted by the BEM algorithm, not only as function of the angle of attack but also as function of the chord-to-radius ratio and the local Rossby number. The data of the lookup table is provided by the measurements of the unsteady aerodynamic experiment Phase-VI, coordinated by the United States' National Renewable Energy Laboratory and conducted in a 24.4m × 36.6m wind tunnel in NASA Ames Research Center. Compared to a well accepted correction model, the proposed methodology predict the load radial distribution with greater accuracy for relatively high wind speeds.

Devido aos efeitos rotacionais, o carregamento observado de seções mais próximas à raiz de asas rotativas é consistentemente maior do que a carga prevista baseada no comportamento aerodinâmico bidimensional do aerofólio correspondente em movimento linear. Portanto, métodos de engenharia usados para analisar e otimizar a aerodinâmica de turbinas eólicas de eixo horizontal (HAWT) dependem de correções para dados de aerofólio 2D. Uma vez que a física associada com o fenômeno não é completamente compreendida, os modelos de correção têm que recorrer a parâmetros determinados empiricamente. É importante enfatizar que uma grande variabilidade das previsões de potência de turbina baseadas em diferentes modelos de correção é observada para condições de elevado carregamento na pá. Propomos uma metodologia para prever o carregamento nas pás de HAWT baseada no amplamente aplicado método blade element momentum (BEM) que não dependa da correção de curvas polares 2D. Na metodologia proposta, os coeficientes de força são armazenados na tabela de consulta e consultados pelo algoritmo BEM, não apenas como função do ângulo de ataque, mas também como função da razão entre a corda e a posição radial e do número de Rossby local. Os dados da tabela de consulta são fornecidos por meio das medidas do experimento aerodinâmico em regime transiente Phase-VI, coordenado pelo laboratório nacional estadunidense de energias renováveis e conduzido em um túnel de vento de 24,4m × 36,6m no Centro de Pesquisa NASA Ames. Comparado a um modelo de correção bem aceito, a metodologia proposta previu a distribuição radial de carregamento com maior acurácia para velocidades do vento relativamente elevadas.
Simulações do método Blade Element Momentum usando polares extraídas a partir de experimentos de modelo de turbina eólica
Keywords: Computational fluid dynamics; Turbulent boundary layer; Energia eólica; Aerodinâmica; Fluidodinâmica computacional; Camada limite turbulenta